Lithium Mining Prospects in Europe and Possible Environmental Consequences - Žnidarič, Davorin; Senegačnik, Marjan (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Lithium is one of the crucial materials for the production of batteries for electric cars as well as for many other devices as are laptops and watches. At present, the share of Europe in the world production of lithium is very small. The majority of lithium is mined in South America, Australia and China. Portugal is the only European country among the world's top ten lithium producers and its share is also very small. However, the stock assessment shows that, in addition to Portugal, some other Europen countries have significant lithium reserves. In view of the expected growing demand for lithium for the production of electric cars, plans are underway to start lithium production in some of these European countries. This will reduce Europe's energy dependence on imports and, on the other hand, have a major impact on the environment. The present article will try also to adreess the problem of environmental justice.